A Novel Chaotic System with Hyperbolic Tangent Terms and Its Application to Random Bit Generator and Image Encryption - Kosmidis, Savvas; Volos, Christos; Moysis, Lazaros; Meletlidou, Efthymia (Journal of Vibration Testing and System Dynamics, 2026)
In this work the study and use of a continuous chaotic dynamical system with no equilibria is presented. In more details the proposed 3-D system has two hyperbolic tangent terms and it has both self excited and hidden attractors. The behavior of the system is studied numerically through phase portraits, bifurcation diagrams and Lyapunov exponents. Also, the design of a random bit generator, based on the chaotic system, is presented. The randomness of the generated bitstream is tested through NIST 800-22. Finally, the random bit generator is used in an image encryption application. The encryption scheme is resistant to various attacks, as it is thoroughly shown.